2022
DOI: 10.1039/d1qi01249e
|View full text |Cite
|
Sign up to set email alerts
|

Organic/inorganic hydrogels by simultaneous self-assembly and mineralization of aromatic short-peptides

Abstract: Self-assembled peptides and proteins have turned out to be excellent templates for the growth of inorganic minerals trying to emulate natural biomineralization processes. Doing this, researchers have developed complex sophisticate...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…Short-peptide supramolecular hydrogels have turned out to be excellent materials with multiple bio- and technological applications. Some of these applications are due to the way these peptides self-assemble to form the hydrogel. In particular, aromatic short-peptides such as Fmoc (fluorenylmethoxicarbonyl)- or Nap (2-naphthylacetic acid)-dipeptides, are extremely versatile, being able to self-assemble under the influence of multiple and diverse stimuli, such as solvent and pH switch, change in temperature, the presence of different salts, the action of enzymes, etc. This versatility has been very useful to develop hydrogels for different applications, such as tissue engineering , and drug delivery, , and to control the type and morphology of the polymeric fibers and the macroscopic and physical properties of the resulting gels. Furthermore, the stimulus process has also been key in obtaining hybrid or composite materials . Composite materials have been obtained mainly by the combination of two different organic materials, such as the combination of two aromatic peptides that can be copolymerized or independently homopolymerized by controlling the stimulus process.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Short-peptide supramolecular hydrogels have turned out to be excellent materials with multiple bio- and technological applications. Some of these applications are due to the way these peptides self-assemble to form the hydrogel. In particular, aromatic short-peptides such as Fmoc (fluorenylmethoxicarbonyl)- or Nap (2-naphthylacetic acid)-dipeptides, are extremely versatile, being able to self-assemble under the influence of multiple and diverse stimuli, such as solvent and pH switch, change in temperature, the presence of different salts, the action of enzymes, etc. This versatility has been very useful to develop hydrogels for different applications, such as tissue engineering , and drug delivery, , and to control the type and morphology of the polymeric fibers and the macroscopic and physical properties of the resulting gels. Furthermore, the stimulus process has also been key in obtaining hybrid or composite materials . Composite materials have been obtained mainly by the combination of two different organic materials, such as the combination of two aromatic peptides that can be copolymerized or independently homopolymerized by controlling the stimulus process.…”
mentioning
confidence: 99%
“…14−18 Furthermore, the stimulus process has also been key in obtaining hybrid or composite materials. 19 Composite materials have been obtained mainly by the combination of two different organic materials, such as the combination of two aromatic peptides that can be copolymerized 20 or independently homopolymerized 21 also been a success, since these peptides can self-assemble in the presence of a multitude of inorganic, metallic, and carbonbased materials. 22,23 Particular types of interesting hybrid hydrogels are those containing carbon nanotubes (CNTs).…”
mentioning
confidence: 99%
“…We have observed a similar process in the biomineralization of hydroxyapatite but in this case mediated by Ca 2+ . 30 Composite hydrogels (Fmoc-FF 20 mM; HmIm/ Zn ratio of 5:1) were also observed by confocal laser scanning microscopy (CLSM) as Fmoc-peptides and ZIF-8 are fluorescent. Figure 3L shows a uniform basal green fluorescence emission from peptide fibers decorated with tiny spherical particles corresponding to ZIF-8 composite particles (see Figure S4 for CLSM of ZIF-8 grown in water and Fmoc-FF hydrogels).…”
Section: Diffusion Protocolmentioning
confidence: 99%
“…All of these factors have contributed to broadening the use of these peptides to develop and explore materials. Another key characteristic of these peptides is their ability to self-assemble under the application of different stimuli, such as solvent or pH switch, addition of salts, or enzymatic reactions. , This can be exploited to induce gelation under physiological conditions, making them highly compatible with biomedical applications . Furthermore, their resulting macroscopic and physical properties can also be affected or tuned by different stimuli offering an extra degree of versatility. , In addition, control over the stimulus-induced transition is also crucial to obtain composite or hybrid hydrogels made by the combination of several organic compounds , or mixtures of organic and inorganic/metallic substrates. , At such, Adams et al have shown that mixtures of different Nap-dipeptides, under specific pH conditions, can form copolymers (co-assembly) or individual homopolymers (self-sorting) based on the relative p K a of the amino acids involved. We have recently shown that Fmoc-FF (Fmoc-diphenylalanine) is able to promote the co-assembly of different Fmoc- and Nap-dipeptides giving rise to hydrogels having different mechanical properties . The mechanism of growth of these peptides usually follows a nucleation–elongation mechanism in which, starting from an initial metastable phase, the formation of fibers is triggered when the conditions allow overpassing the free energy barrier of polymerization. We have shown that metastable intermediates formed by the combination of two different peptides had a lower free energy barrier of polymerization; therefore, the co-assembly was favored vs the self-assembly of individual peptides .…”
Section: Introductionmentioning
confidence: 99%